A flux-cored wire for flat or horizontal welding of a 490 MPa grade steel base material and a method for manufacturing the same
By preparing flux-cored welding wire with a specific formula, the problem of low welding efficiency in medium and heavy plates has been solved, achieving efficient and aesthetically pleasing weld formation and excellent mechanical properties. It is suitable for welding medium and heavy plates with 490MPa grade steel base material and is applicable to fields such as mechanical engineering, bridge construction, petrochemicals, and marine engineering.
Patent Information
- Application Number
- CN202410119760.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-29
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-01-29
AI Technical Summary
Existing welding methods for medium and heavy plates suffer from low metal cladding efficiency, long production time, and excessive heat input in submerged arc welding, making them unsuitable for high-strength steel and complex structure welding, thus limiting the application and development of medium and heavy plates.
A flux-cored welding wire with a specific formula, including components such as quartz sand, rutile, potassium sodium titanate, aluminum iron, silicon iron, sodium cryolite, silicon-calcium alloy, iron sand, metallic bismuth, electrolytic manganese, nickel powder, and manganese dioxide, is prepared by high-temperature calcination and baking treatment. This flux-cored welding wire is suitable for flat or horizontal welding of medium and thick plates with a base material of 490MPa steel and is used for CO2 gas shielded welding.
It achieves high-efficiency welding, produces aesthetically pleasing welds, facilitates slag removal, is suitable for automated and semi-automated welding, has high welding efficiency, and the weld metal possesses excellent mechanical properties and moisture resistance, meeting national standards and significantly improving welding efficiency.
Smart Images

Figure BDA0004686328560000061 
Figure BDA0004686328560000071 
Figure BDA0004686328560000072
Abstract
Description
Technical Field
[0001] This invention relates to the field of steel welding technology, specifically to a flux-cored welding wire suitable for flat or horizontal welding of medium-thick plates with a base material of 490MPa grade steel, and its preparation method. Background Technology
[0002] Medium and heavy plates are widely used in mechanical engineering, bridge construction, petrochemicals and marine engineering. The usage of medium and heavy plates accounts for about 10% of the total annual steel usage, and this figure is on the rise.
[0003] The existing welding methods for producing and using medium and heavy plates are mainly the following three:
[0004] The first two methods involve welding in partially flat positions using submerged arc welding, either by manual arc welding or by CO2 gas shielded welding with small-gauge welding wire.
[0005] The above two welding methods have relatively low metal cladding efficiency and long production time.
[0006] The third method is submerged arc welding. However, submerged arc welding has a large heat input and is not suitable for use on high-strength steel with high welding quality requirements. In addition, this welding method has great limitations and cannot be used for welding in complex structural positions. It can only be used for flat welding under the conditions allowed by the submerged arc equipment.
[0007] Therefore, the current welding process for medium and heavy plates is not suitable for the application and development of medium and heavy plates, which restricts the work efficiency in the production and use of medium and heavy plates. Summary of the Invention
[0008] In order to overcome the above-mentioned defects of the prior art, the purpose of this invention is to provide a flux-cored welding wire suitable for flat or horizontal welding of medium and thick plates with 490MPa grade steel base material.
[0009] A flux-cored welding wire suitable for flat or horizontal welding of medium-thick plates with a base material of 490MPa steel, wherein the composition of the flux-cored welding wire, calculated by weight percentage, includes the following components:
[0010] Quartz sand 5-8%;
[0011] Rutile 18-22%;
[0012] Potassium sodium titanate 2-4%;
[0013] Aluminum and iron content: 4-6%;
[0014] Ferrosilicon 2-4%;
[0015] Sodium ice crystals 1-2%;
[0016] 3-5% silicon-calcium alloy;
[0017] Iron sand 1-3%;
[0018] Bismuth metal 0.1-0.3%;
[0019] Electrolytic manganese 10-14%;
[0020] Nickel powder 0.5-1.5%;
[0021] 2-4% manganese dioxide;
[0022] The remainder is iron powder.
[0023] In a preferred embodiment of the present invention, the quartz sand has a melting point of 1700-1720℃ and a relative density of 2.60-2.70.
[0024] In a preferred embodiment of the present invention, the aluminum-iron has a melting point of 655-660°C and a relative density of 2.6-2.8.
[0025] In a preferred embodiment of the present invention, the ferrosilicon has a melting point of 1410-1430°C and a relative density of 2.4-2.5.
[0026] In a preferred embodiment of the present invention, the melting point of the nickel powder is 1450-1460°C.
[0027] In a preferred embodiment of the present invention, the iron powder is reduced iron powder or atomized iron powder.
[0028] A method for preparing flux-cored welding wire suitable for flat or horizontal welding of medium-thick plates with 490MPa grade steel base material includes the following steps:
[0029] The first step involves calcining the quartz sand and rutile at high temperature to remove the water of crystallization and adsorbed water in the minerals until the moisture content of the quartz sand and rutile does not exceed 0.01%.
[0030] The second step is to bake the potassium sodium titanate and sodium ice crystals to remove the adsorbed moisture from the potassium sodium titanate and sodium ice crystals themselves.
[0031] The third step involves mixing the products from the first and second steps with the remaining components to obtain a powder, which is then baked. The baked powder is then filled into the steel strip at a ratio of 16.5-17.5% to obtain the welding wire product.
[0032] In a preferred embodiment of the present invention, the diameter of the welding wire product is 2.0-2.5 mm, preferably 2.4 mm.
[0033] The beneficial effects of this invention are as follows:
[0034] 1. This invention, through the rational design of the proportions of various slag-forming agents and ferroalloys in the formula, enables the welding wire of this invention to have good welding processability. The welding positions are flat welding and horizontal welding. This flux-cored welding wire uses CO2 gas protection and the welding positions are flat welding and horizontal welding. The weld formation is beautiful and the slag removal is easy. It can be used for welding medium and thick plates of 490MPa grade steel base material. It can be used for automated welding and semi-automated welding, and has strong applicability.
[0035] The medium-thick plate referred to in this invention is a steel plate with a thickness of 4.5-25.0 mm.
[0036] 2. The welding wire of this invention has a diameter of 2.4 mm and the proportion of iron alloy in the flux core is significantly higher than that of existing rutile flux-cored welding wires, accounting for more than 60%, which has extremely high deposition efficiency and welding efficiency.
[0037] 3. The weld metal of this invention under high heat input welding has the following excellent mechanical properties:
[0038] Tensile strength Rm: 490-660 (MPa), yield strength ReL: ≥390 (MPa), elongation A: ≥22%, low temperature impact AKV at -30℃: ≥27 (J), diffusible hydrogen content: ≤8mL / 100g, meeting national standards.
[0039] 4. In this invention, the deoxidizer does not use easily hygroscopic powders such as magnesium powder and aluminum-magnesium alloy, but uses iron alloys such as aluminum-iron for deoxidation. This makes the welding wire prepared by this invention have good moisture resistance, can be exposed to air for a long time without producing defects such as porosity, and has a fast melting speed and high welding efficiency.
[0040] It is significantly more efficient than existing rutile flux-cored welding wires and has advantages such as convenience and economy that submerged arc welding wires do not possess. Detailed Implementation
[0041] The present invention will be further described below with reference to specific embodiments:
[0042] The working principle of this invention is as follows:
[0043] Quartz sand:
[0044] The quartz sand in this embodiment of the invention has a melting point of 1710℃ and a relative density of 2.65.
[0045] In the welding metallurgical process, it mainly plays the role of slag formation, reacting with iron oxide to remove gas from the weld and speeding up the welding speed. An appropriate amount of quartz sand can also increase the activity of the slag.
[0046] Rutile:
[0047] In the welding process, rutile mainly functions to form slag, stabilize the arc, and reduce welding spatter. Rutile has good hot slag removal properties, a stable arc, a calm molten pool, good directional welding, and excellent weld formation. If too much is added, it will cause the slag to become too sticky, resulting in poor slag fluidity; if too little is added, it will not be able to form slag or stabilize the arc, affecting the process performance of the welding material. Therefore, after extensive research, the inventors of this invention selected an addition ratio of 18-22%.
[0048] Potassium sodium titanate:
[0049] Because K+ and Na+ are low-ionization ions, they can further protect the electric arc, concentrate the arc, and enable good welding process. In the welding metallurgy process, the gas generated by the decomposition of carbonates can also protect the weld pool.
[0050] Aluminum Iron:
[0051] Aluminum has a melting point of 658℃ and a relative density of 2.7. It plays a major role in welding metallurgy.
[0052] It has a stronger deoxidizing ability than Ti, and the exothermic oxidation process accelerates the melting speed of the welding wire, which can prevent the diffusion of N into the weld metal.
[0053] Ferrosilicon:
[0054] Silicon has a melting point of 1420℃ and a relative density of 2.42. It is the main source of silicon in weld metal. On the one hand, silicon has a deoxidizing effect, and on the other hand, it also strengthens the weld. However, adding too much silicon will increase the acidity and viscosity of the slag due to the SiO2 generated by the reaction. Therefore, if the silicon content in the weld is too high, it will affect the toughness and crack resistance of the weld metal.
[0055] Therefore, after extensive research, the inventors of this invention selected an addition ratio of 2-4%.
[0056] Sodium ice crystals:
[0057] Its main component, fluoroaluminate, contains F, which can react with H+ in the molten pool or droplets to form HF vapor, which has a good dehydrogenation effect and a dilution effect on the molten pool.
[0058] However, if the fluoride content in the overall formula is too high, it will cause unstable arc, larger spatter, and worse arc sound during welding. The best effect can be achieved by controlling the amount of sodium ice crystals added within 1-2% of the range of this invention.
[0059] Silicon-calcium alloy:
[0060] When silicon-calcium alloy is added as a deoxidizer, excessive amounts can lead to an excessive amount of calcium oxide entering the welding slag.
[0061] Therefore, after extensive research, the inventors of this invention selected an addition ratio of 3-5%, which can effectively increase the basicity of the slag while improving its crack resistance.
[0062] iron sand:
[0063] It can accelerate welding speed and penetration. In addition, it can also decarburize, dilute slag, and form slag.
[0064] Bismuth metal:
[0065] The addition of bismuth increases the coefficient of slag expansion and is a good slag remover, making it easy to remove slag from the weld of the high-efficiency welding flux-cored wire in this invention and resulting in a beautiful weld formation.
[0066] Electrolytic manganese:
[0067] Electrolytic manganese is the main deoxidizer in the weld metal composition, used to reduce the oxygen content, increase the strength and crack resistance of the weld metal, improve low-temperature impact toughness, and regulate the fluidity of molten iron. On the one hand, it increases the amount of acicular ferrite while correspondingly reducing the amount of proeutectoid ferrite and layered components, refining the microstructure of the acicular ferrite and coarse-grained regions of the weld, thus improving the impact toughness of the weld. It also plays a role in desulfurization in welding metallurgy.
[0068] Nickel powder:
[0069] The nickel powder used in this embodiment of the invention has a melting point of 1452°C. It has a lower affinity for oxygen than iron, making it less prone to oxidation during welding and resulting in a high transition coefficient.
[0070] As a major source of Ni in weld metal, Ni is an important alloying element in weld deposited metal. Through solid solution toughening, it improves the strength and toughness of the weld metal, especially its low-temperature toughness, which increases with increasing nickel content within a certain range. Within the scope of this invention, it can effectively improve low-temperature impact toughness.
[0071] Manganese dioxide:
[0072] Through extensive research, the inventors of this invention have discovered that manganese dioxide used within the scope of this invention can help remove impurities in welding metallurgy, improve weld quality, stabilize the welding arc, and accelerate the welding speed.
[0073] Iron powder:
[0074] Adding iron powder to the flux core can improve welding deposition efficiency, stabilize the arc, and reduce spatter. In order to ensure high deposition efficiency, the inventors of this invention have determined the proportion of iron powder in the flux core through extensive research. This proportion is higher than that in general welding wire components, and mainly comes from reduced iron powder or atomized iron powder.
[0075] The present invention will be further described below through specific embodiments:
[0076] Examples 1-3:
[0077] Preparation of a high-efficiency flux-cored welding wire.
[0078] 1. The methods in Examples 1-3 are as follows:
[0079] Quartz sand and rutile are calcined at 900℃ in a rotary kiln to remove the crystal water and adsorbed water in the minerals.
[0080] Rotary calcining furnaces offer advantages over box furnaces. At 900℃, the furnace body rotates continuously at a set frequency, ensuring uniform heating of the calcined material and resulting in extremely low moisture content; for example, the moisture content of quartz sand and rutile does not exceed 0.01%.
[0081] This ensures that the hydrogen content of the mineral powder in the flux-cored wire is extremely low, thus guaranteeing the low hydrogen content of this invention.
[0082] In addition, potassium sodium titanate and sodium ice crystals are baked at 500°C in a box-type high-temperature furnace to remove the adsorbed moisture from the potassium sodium titanate and sodium ice crystals themselves.
[0083] Table 1 shows the core proportions in Examples 1-3:
[0084]
[0085] Prepare the medicine powder according to the proportions in Table 1, mix it thoroughly with a small V-type mixer, bake it at 200℃ for 2 hours, and use a carbon steel strip with a specification of 0.8×14mm (chemical composition as shown in Table 2 below). Through the forming process, fill the steel strip with medicine powder at a ratio of 16.5-17.5% and draw it to a direct specification of 2.4mm.
[0086] Table 2 shows the content of various chemical components in special carbon steel strip:
[0087] element C Mn Si S P content(%) 0.02-0.04 0.15-0.35 ≤0.35 ≤0.008 ≤0.008
[0088] 2. Weld test plates according to the requirements of Chinese national standard GB / T10045-2018 and AWS A5.20-2021. The chemical composition and mechanical properties of the deposited metal are shown in Tables 3 and 4.
[0089] Table 3 shows the chemical composition content of Examples 1-3:
[0090]
[0091] Table 4 Mechanical properties of Examples 1-3
[0092]
[0093] 3. The ISO3690 thermal conductivity method for hydrogen diffusion was used to test Examples 1-3. The specific test results are shown in Figure 5.
[0094] Table 5. Results of hydrogen diffusion test using the ISO 3690 thermal conductivity method:
[0095] ISO 3690 Thermal Conductivity Method Example 1 Example 2 Example 3 Diffusible hydrogen content (ml / 100g) 5.7 6.3 6.0
[0096] 4. Welding efficiency tests were conducted on existing rutile flux-cored wires and Examples 1-3. The specific test results are shown in Table 6.
[0097] Table 6 Welding efficiency test
[0098]
[0099] The above shows and describes the basic principles and main features of the invention and the advantages of the invention. The flux-cored wire of the present invention is significantly different from the existing rutile flux-cored wire for 490MPa grade steel in terms of deposition efficiency.
[0100] Provided that the mechanical properties meet the requirements, its hourly deposition efficiency is more than 1.5 times that of the current 1.6mm welding wire.
[0101] Under welding parameters of 400-600A welding current and 44-50V welding voltage, its mechanical properties, process properties, and crack resistance are fully guaranteed, meeting both Chinese and American national standards. Its specific performance characteristics are as follows:
[0102] Tensile strength Rm: 490-660 (MPa), ReL: ≥390 (MPa), elongation A ≥22%, low temperature impact energy AKV ≥27 (J) at -30℃, diffusible hydrogen content ≤8mL / 100g.
[0103] 5. Comparative sample 1 (deoxidized with magnesium powder) and comparative sample 2 (deoxidized with aluminum-magnesium alloy) flux-cored welding wires (2.4mm specification) and Examples 1-3 were placed in the air (average air humidity 70%) and a porosity sensitivity test was conducted. The specific test results are shown in Table 7.
[0104] Table 7 Stomatal Sensitivity Test
[0105]
[0106] The results of the porosity sensitivity test show that the control sample No. 1, which uses magnesium powder for deoxidation, and the control sample No. 2, which uses aluminum-magnesium alloy for deoxidation, are significantly different from the control samples 1-3 in terms of moisture resistance. This also verifies that the control samples 1-3 of the present invention have good moisture resistance.
Claims
1. A flux-cored welding wire suitable for flat or horizontal welding of medium-thick plates with a base material of 490MPa steel, wherein the composition of the flux-cored welding wire, calculated by weight percentage, is characterized in that... It includes the following components: Quartz sand 5-8%; Rutile 18-22%; Potassium sodium titanate 2-4%; Aluminum and iron 4-6%; Ferrosilicon 2-4%; Sodium ice crystals 1-2%; 3-5% silicon-calcium alloy; Iron sand 1-3%; Bismuth metal 0.1-0.3%; Electrolytic manganese 10-14%; Nickel powder 0.5-1.5%; Manganese dioxide 2-4%; The remainder is iron powder.
2. The flux-cored welding wire as described in claim 1, suitable for flat or horizontal welding of medium-thick plates with a base material of 490MPa steel, is characterized in that... The quartz sand has a melting point of 1700-1720℃ and a relative density of 2.60-2.
70.
3. The flux-cored welding wire as described in claim 1, suitable for flat or horizontal welding of medium-thick plates with a base material of 490MPa steel, is characterized in that... The aluminum-iron has a melting point of 655-660℃ and a relative density of 2.6-2.
8.
4. The flux-cored welding wire as described in claim 1, suitable for flat or horizontal welding of medium-thick plates with a base material of 490MPa steel, is characterized in that... The ferrosilicon has a melting point of 1410-1430℃ and a relative density of 2.4-2.
5.
5. The flux-cored welding wire as described in claim 1, suitable for flat or horizontal welding of medium-thick plates with a base material of 490MPa steel, characterized in that, The melting point of the nickel powder is 1450-1460℃.
6. The flux-cored welding wire as described in claim 1, suitable for flat or horizontal welding of medium-thick plates with a base material of 490MPa steel, is characterized in that... The iron powder is reduced iron powder or atomized iron powder.
7. A method for preparing a flux-cored welding wire suitable for flat or horizontal welding of medium-thick plates with a base material of 490MPa steel, as described in any one of claims 1-6, characterized in that... Includes the following steps: The first step involves calcining the quartz sand and rutile at high temperature to remove the water of crystallization and adsorbed water from the minerals until the moisture content of the quartz sand and rutile does not exceed 0.01%. The second step is to bake the potassium sodium titanate and sodium ice crystals to remove the adsorbed moisture from the potassium sodium titanate and sodium ice crystals themselves. The third step involves mixing the products from the first and second steps with the remaining components to obtain a powder, which is then baked. The baked powder is then filled into the steel strip at a ratio of 16.5-17.5% to obtain the welding wire product.
8. The method for preparing a flux-cored welding wire suitable for flat or horizontal welding of medium-thick plates with a base material of 490MPa steel, as described in claim 7, is characterized in that... The diameter of the welding wire product is 2.0-2.5mm.
Citation Information
Patent Citations
Full-position soldering biphase stainless steel flux-cored wire
CN101134271A
Rutile flux-cored wire with tensile strength of 800 MPa grade and preparation method thereof
CN107914099A
